Analysis of Iot-Based Soil Moisture Data Visualization and Network Stability Effects on Precision Irrigation Monitoring - Nurwahdaniah Maulida; Joko Sutopo (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
The Internet of Things (IoT) technology has enhanced precision irrigation monitoring by enabling real-time soil moisture measurement. However, the reliability of historical data visualization is strongly influenced by network stability between sensors and data servers. This study analyzes soil moisture trend visualization based on an IoT system and evaluates the effect of network stability on data consistency. Soil moisture data were obtained using a capacitive sensor integrated with an ESP32 microcontroller and transmitted via a Wi-Fi network. Data trends were visualized using time-series graphs, while network performance parameters, including latency, packet loss, and transmission delay, were analyzed. The results indicate that network instability causes data loss and irregular visualization patterns, which may affect irrigation monitoring accuracy. Therefore, improving network reliability is essential for sustainable precision agriculture systems.